Preparation method and application of in-situ constructed MXene-based metal boride electrocatalyst

By constructing the MXene-based metal boride electrocatalyst in situ, and using boron thermal reduction method to generate the dicobalt boride@MXene heterostructure, the existing cobalt-based electrocatalyst has solved the problem of low reaction efficiency and insufficient catalyst stability in the nitrate reduction synthesis process, and achieved efficient ammonia yield and Faraday efficiency.

CN119913545APending Publication Date: 2025-05-02HEBEI UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510089357.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-21
Publication Date
2025-05-02

AI Technical Summary

Technical Problem

During the nitrate reduction and synthesis of ammonia, the existing cobalt-based electrocatalysts have low reaction efficiency and insufficient catalyst stability, which fail to achieve deep removal of nitrate and efficient directional conversion of ammonia.

Method used

By constructing the MXene-based metal boride electrocatalyst in situ, the residual cobalt metal was grown in situ into dicobalt boride by boron thermal reduction method, forming a dicobalt boride@MXene heterostructure electrocatalyst. This method simplifies the catalyst preparation process and improves the structural stability and catalytic activity of the catalyst.

Benefits of technology

The electrocatalyst exhibits high ammonia yield and Faraday efficiency in the electrocatalytic nitrate reduction reaction, with ammonia yield reaching 7340μg h-1mgcat-1 and Faraday efficiency reaching 93.97%, which significantly improves the efficiency of nitrate reduction.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119913545A_ABST
    Figure CN119913545A_ABST
Patent Text Reader

Abstract

The invention relates to a preparation method and application of an in-situ constructed MXene-based metal boride electrocatalyst. According to the method, a Ti3AlC2MAX precursor is etched into MXene through a molten salt etching strategy, and then cobalt metal left on the MXene grows into dicobalt boride in situ through a boron thermal reduction method. The electrocatalyst prepared by the invention has rapid electron transfer kinetics, abundant catalytic active sites and excellent structural stability, and shows high ammonia yield in an electrocatalytic nitrate reduction reaction, thereby providing possibility for green and sustainable development of ammonia synthesis.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of electrocatalytic nitrate reduction to synthesize ammonia, and in particular to a preparation method and application of a two-dimensional dicobalt boride@MXene heterostructure electrocatalyst. Background Art

[0002] Ammonia is widely used in chemical raw materials, pharmaceutical manufacturing, fertilizer production and other fields. The main method for producing ammonia is the Haber-Bosch process, which is carried out under high temperature (400-600°C) and high pressure (100-350atm). Due to its energy-intensive characteristics, the annual energy consumption of this process accounts for about 1-2% of the global energy consumption. Therefore, it is particularly important to explore a clean and efficient ammonia synthesis strategy. Using clean energy as the driving force, the nitrogen reduction reaction is environmentally friendly and is considered to be a green alternative to the Haber-Bosch ammonia synthesis process. However, the extremely high stability of the N≡N triple bond (941KJ·mol -1 ) and the low solubility of nitrogen in aqueous solution limit the ammonia production and Faradaic efficiency. Nitrate, a widespread groundwater pollutant, is considered a promising alternative. Compared with the nitrogen reduction reaction, the low N=O binding energy (204 kJ·mol -1 ) and high nitrate solubility improve the reaction kinetics of ammonia synthesis. However, it involves a complex reaction pathway involving the coupled transfer of nine protons and eight electrons. Therefore, it is urgent to develop catalysts with high selectivity and high activity for nitrate reduction to synthesize ammonia.

[0003] Cobalt-based electrocatalysts have attracted much attention due to their low cost and high active hydrogen contribution rate in nitrate reduction. In recent years, related technologies for the electrocatalytic reduction of nitrates to synthesize ammonia using cobalt-based catalysts have also been reported. Patent CN114369841B uses foamed cobalt and oxalic acid as raw materials to prepare a cobalt nanowire material, which is used for the electrocatalytic reduction of nitrates to synthesize ammonia. However, the electrocatalyst prepared from this material only showed an 84.1% nitrate removal rate after 6 hours of reaction, and failed to achieve deep removal of nitrates and efficient directional conversion of ammonia. Therefore, there is an urgent need to design and develop an efficient cobalt-based electrocatalyst to improve the efficiency of nitrate reduction. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing MXene-based metal boride electrocatalysts in situ by using a molten salt etching strategy to prepare Ti 3 AlC 2The MAX precursor is etched into MXene, and then the cobalt metal remaining on the MXene is grown in situ into dicobalt boride by boron thermal reduction. The electrocatalyst prepared by the present invention has fast electron transfer kinetics, abundant catalytic active sites and excellent structural stability, and exhibits a high ammonia yield in the electrocatalytic nitrate reduction reaction, which provides the possibility for the green and sustainable development of ammonia synthesis.

[0005] The present invention provides the following technical solutions:

[0006] A method for preparing an in-situ constructed MXene-based metal boride electrocatalyst, the method comprising the following steps:

[0007] Step 1: Ti 3 AlC 2 MAX, CoCl 2 6H 2 O, NaCl, and KCl were added to a mortar and ground in a glove box for 15–30 min to obtain a homogeneous mixture;

[0008] Among them, Ti 3 AlC 2 MAX, CoCl 2 6H 2 The molar ratio of O, NaCl, and KCl is 1:3:2:2;

[0009] Step 2: annealing the mixture obtained in step 1 at 700-800° C. for 20-30 hours in an argon atmosphere, then washing with deionized water and freeze-drying to obtain cobalt@MXene;

[0010] Step 3: The cobalt@MXene, boron powder, NaCl and KCl prepared in step 2 are mixed and ground to obtain a mixture;

[0011] The sum of the masses of NaCl and KCl is 8 to 12 times the sum of the masses of cobalt@MXene and boron powder; the molar ratio of NaCl to KCl is 1:0.8 to 1.2; the mass ratio between cobalt@MXene and boron powder is 8:0.9 to 1.1;

[0012] Step 4: The mixture obtained in step 3 is annealed in an argon atmosphere at a temperature of 900 to 1000° C. for 1 to 2 hours; then washed with deionized water and freeze-dried to obtain dicobalt boride@MXene.

[0013] The dicobalt boride@MXene electrocatalyst prepared by the method is used for electrocatalytic reduction of nitrate to synthesize ammonia.

[0014] Specifically, the process comprises the following steps: electrolyzing the electrolyte for 0.5 to 2 hours under a three-electrode system and constant voltage to obtain ammonia; wherein carbon paper loaded with a catalyst, Ag / AgCl, and platinum wire are used as a working electrode, a reference electrode, and a counter electrode, respectively; and the diaphragm is a Nafion117 membrane;

[0015] The electrolyte is composed of a 0.1-1.0 M potassium sulfate solution containing 0.01-0.10 M potassium nitrate; 0.5-1 mg of catalyst is loaded per 1 square centimeter; all potentials are reversible hydrogen electrode (RHE), and the conversion formula is E(RHE)=E(Ag / AgCl)+0.222+0.059×pH; the voltage range of electrolysis is -0.3V~-0.7V.

[0016] The essential features of the present invention are:

[0017] The present invention firstly performs high temperature annealing in an argon atmosphere, and CoCl 2 6H 2 Co in O molten salt 2+ With Ti 3 AlC 2 The Al atoms in MAX undergo redox reactions, where Co 2+ is reduced to Co nanoparticles, while Al is oxidized to AlCl 3 The reaction mixture is evaporated at high temperature, then washed with deionized water and freeze-dried to obtain cobalt@MXene. The cobalt@MXene is then annealed with boron powder at high temperature to in-situ borate the residual cobalt on the surface of the MXene to generate dicobalt boride. The present invention does not need to eliminate the metal particles between the MXene layers after molten salt etching. By turning waste into treasure, the residual cobalt nanoparticles after molten salt etching are cleverly converted into dicobalt boride@MXene heterostructure catalysts and active sites for reducing nitrates. Compared with the traditional method of etching MAX with a fluorine-containing acidic solution, the experimental safety and environmental protection are greatly improved.

[0018] The present invention has the following beneficial effects:

[0019] 1. The preparation of the electrocatalyst of the present invention only involves a simple calcination method, which greatly simplifies the catalyst preparation process and saves time and cost.

[0020] 2. The present invention cleverly utilizes the residual cobalt nanoparticles after molten salt etching through the strategy of turning waste into treasure, and generates a dicobalt boride catalyst supported on MXene and an active site for reducing nitrate through in situ boron thermal reduction, which not only avoids the treatment of the metal after etching, but also effectively utilizes the characteristics of the metal.

[0021] 3. Due to the metal-support interaction, the cobalt diboride nanoparticles in situ loaded on MXene are not easy to agglomerate during the electrocatalytic process, thereby improving the electrocatalytic activity of the material. At the same time, the high conductivity and structural support of MXene ensure the structural stability of the material, and the current density has not decayed after 65 hours of electrolysis experiment.

[0022] 4. Boron sites can effectively adsorb and activate nitrate ions, accelerate the deoxygenation step of the nitrate reduction reaction, and reduce the energy barrier for the dissociation of nitrogen oxides. Cobalt sites help dissociate water and produce active hydrogen for the hydrogenation step of the nitrate reduction reaction, ensuring that there is enough active hydrogen to combine with nitrogen oxides after they dissociate, thereby smoothly generating ammonia products. Therefore, the material showed a satisfactory ammonia yield (7340 μg h -1 mg cat -1 ) and Faradaic efficiency (93.97%), which makes possible the green and sustainable development of ammonia synthesis. BRIEF DESCRIPTION OF THE DRAWINGS

[0023] Figure 1 X-ray diffraction patterns of the electrocatalysts of Example 1 and Example 2.

[0024] Figure 2 This is a scanning electron microscope image of the electrocatalyst prepared in Example 1.

[0025] Figure 3 This is the linear sweep voltammetry curve of the electrocatalyst prepared in Example 1 in an electrolyte.

[0026] Figure 4 The yield of ammonia synthesis of the electrocatalyst prepared in Example 1.

[0027] Figure 5 The Faraday efficiency of ammonia synthesis of the electrocatalyst prepared in Example 1.

[0028] Figure 6 The cycling stability of the electrocatalyst prepared in Example 1. DETAILED DESCRIPTION

[0029] The specific implementation steps and drawings of the present invention are described in full and clearly below. It is necessary to point out that the specific implementation of the present invention cannot be limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, other embodiments or inferences obtained without making innovative ideas should be considered to belong to the protection scope of the present invention.

[0030] The Ti of the present invention 3 AlC 2MAX (titanium carbide aluminum) is a well-known material and is commercially available. The present invention uses a product of Jilin Yiyi Technology Co., Ltd., but is not limited thereto.

[0031] Embodiment 1:

[0032] The specific preparation method of dicobalt boride@MXene electrocatalyst is as follows:

[0033] Step (1): 1g of Ti 3 AlC 2 MAX (i.e. 0.005 mol), 3.67 g (i.e. 0.015 mol) of CoCl 2 6H 2 O, 0.6 g (0.01 mol) of NaCl and 0.77 g (0.01 mol) of KCl were added to a mortar and fully ground in a glove box for 20 minutes to obtain a uniform mixture. The above mixture was transferred to a corundum boat and placed in a tube furnace. The tube furnace was sealed and filled with argon, annealed at 750 ° C for 24 hours, and then washed with deionized water and freeze-dried to obtain cobalt@MXene.

[0034] Step (2): 0.2 g of cobalt@MXene, 0.025 g of boron powder, 0.99 g of NaCl and 1.26 g of KCl were added to a mortar and fully ground in a glove box for 20 minutes to obtain a uniform mixture (i.e., the sum of the mass of NaCl and KCl is 10 times that of cobalt@MXene and boron powder, and the molar ratio of NaCl to KCl is 1:1). The above mixture was transferred to a corundum boat and placed in a tube furnace, which was sealed and filled with argon, annealed at 950°C for 1.5 hours, and then washed with deionized water and freeze-dried for 24 hours to obtain a dicobalt boride@MXene heterostructure.

[0035] The X-ray diffraction pattern was used to analyze the heterostructure of cobalt diboride@MXene. Figure 1 As shown in the figure, the (002) characteristic peak at 7.89° is attributed to the MXene successfully obtained by etching, and the four characteristic peaks at 27.66°, 35.85°, 42.95° and 45.88° correspond to the (101), (200), (002) and (211) crystal planes of dicobalt boride, respectively (PDF#75-1063). The above characterization results prove the successful preparation of dicobalt boride@MXene heterostructure.

[0036] The morphology of the dicobalt boride@MXene heterostructure was observed using a scanning electron microscope. Figure 2As shown in Figure 2, dicobalt boride nanoparticles are distributed between the layers of MXene. The layered structure of MXene not only improves the structural stability, but also can disperse dicobalt boride nanoparticles. The cobalt site and the boron site have a tandem catalytic effect, which effectively improves the NO 3 RR performance.

[0037] The electrochemical performance of dicobalt boride@MXene electrocatalyst was analyzed by linear sweep voltammetry. Figure 3 As shown, compared with Co@MXene, CoB2@MXene exhibited a large current density, indicating that CoB2@MXene electrocatalyst has excellent nitrate reduction activity.

[0038] The specific steps include:

[0039] Step 1: Electrocatalytic reduction of nitrate to synthesize ammonia was performed on a CHI-760E electrochemical workstation using a three-electrode system. 2 Carbon paper-supported catalyst, Ag / AgCl and platinum wire were used as working electrode, reference electrode and counter electrode, respectively.

[0040] Step 2: In a solution containing 0.1M KNO 3 and 0.1MK 2 SO 4 Electrocatalytic tests were carried out in an h-type electrolytic cell separated by a Nafion 117 membrane and an electrolyte of 5 wt % H at 80 °C. 2 O 2 The samples were treated in the solution for 1 hour, then immersed in deionized water for 30 minutes, and then heated at 80 °C for 1 h. 2 SO 4 The samples were immersed in deionized water at 80 °C for 30 min.

[0041] Step 3: Disperse 10 mg of catalyst in a mixed solution (0.45 mL of anhydrous ethanol + 0.45 mL of deionized water + 50 μL of Nafion solution) to prepare a working electrode. After ultrasonic treatment for 1 hour, a uniform ink is formed. Drop 50 μL of catalyst ink on a 1×1 cm 2 All potentials in this work are reversible hydrogen electrode (RHE), and the conversion formula is E(RHE) = E(Ag / AgCl) + 0.222 + 0.059 × pH.

[0042] Step 4: Perform a chronoamperometric test at different potentials for 1 hour. After 1 hour of electrolysis, take out 2 mL of the electrolyte and perform qualitative and quantitative analysis of ammonia in the electrolyte by UV spectrophotometry.

[0043] The amount of ammonia synthesis in the electrolyte after electrolysis of the cobalt boride@MXene electrocatalyst at constant voltage was detected using an ultraviolet spectrophotometer. Figure 4 As shown in Figure 2, the ammonia yield of the cobalt diboride@MXene electrocatalyst at −0.7 V reached 7340 μg h -1 mg cat -1 , which makes sustainable and large-scale ammonia synthesis possible. Figure 4 The cobalt diboride@MXene and cobalt@MXene involved in the electrolysis test were loaded on carbon paper. The electrolysis system was a three-electrode system. The electrolysis instrument was a CHI-760E electrochemical workstation. The electrolysis test method was constant voltage. The constant voltage electrolysis range was the same, -0.3V to -0.7V. The composition of the electrolyte was the same, containing 0.1M KNO 3 0.1MK 2 SO 4 The ammonia yield after electrolysis is measured by an ultraviolet spectrophotometer.

[0044] The Faradaic efficiency was calculated using the ammonia yield of the cobalt diboride@MXene electrocatalyst at different voltages. Figure 5 As shown in Figure 2, the Faradaic efficiency of the dicobalt boride@MXene electrocatalyst at -0.5 V is as high as 93.97%, further demonstrating its excellent NO 3 The selectivity of RR can effectively inhibit the occurrence of hydrogen evolution side reaction.

[0045] In order to study the electrochemical stability of dicobalt boride@MXene, chronoamperometric tests were performed. Figure 6 As shown, the current density fluctuation of the cobalt boride@MXene electrocatalyst is minimal during the 65-hour test, which strongly proves that the structure of the electrocatalyst remains stable during the long-term electrocatalytic process.

[0046] Embodiment 2:

[0047] The steps are the same as step (1) of Example 1, and the obtained sample is a cobalt@MXene heterostructure.

[0048] The cobalt@MXene heterostructure was analyzed using X-ray diffraction patterns. Figure 1 As shown, the (002) characteristic peak at 7.89° is attributed to the MXene successfully obtained by etching, and the characteristic peaks at 44.25°, 51.64° and 75.88° are attributed to the (111), (200) and (220) crystal planes of cobalt. The above characterization results prove the successful preparation of cobalt@MXene heterostructure.

[0049] The electrochemical performance of cobalt@MXene electrocatalysts was analyzed by linear sweep voltammetry. Figure 3 As shown, the current density of Co@MXene at each potential is smaller than that of Cobalt diboride@MXene, indicating that the nitrate reduction activity of Co@MXene electrocatalyst is lower than that of Cobalt diboride@MXene.

[0050] The amount of ammonia synthesis in the electrolyte after electrolysis of the cobalt@MXene electrocatalyst at different constant voltages was detected using an ultraviolet spectrophotometer. Figure 4 As shown in Figure 2, the ammonia yield of the Co@MXene electrocatalyst at −0.7 V was 3005 μg h -1 mg cat -1 .

[0051] The Faradaic efficiency was calculated using the ammonia yield of the Co@MXene electrocatalyst at different voltages. Figure 5 As shown, the cobalt@MXene electrocatalyst exhibited a Faradaic efficiency of 74.56% at -0.5 V.

[0052] The ammonia yield and Faradaic efficiency of the Co@MXene heterostructure at −0.5 V were 1936 μg h -1 mg cat -1 The boron in the metal boride contributes to the adsorption of nitrate and the deoxidation process in nitrate reduction. Therefore, the reason for the performance degradation in Example 2 is that the lack of boron hinders the conversion of nitrogen-containing intermediates into ammonia, resulting in performance degradation.

[0053] Embodiment 3:

[0054] The other steps were the same as step (1) and step (2) of Example 1, except that the amount of boron powder added was replaced by 0.010 g from 0.025 g. The ammonia yield of the obtained material was 6218 μg h at -0.7 V. -1 mg cat -1 , the Faradaic efficiency is 85.91%. The ammonia yield at -0.5 V is 4160 μg h -1 mg cat -1 , the Faraday efficiency is 89.45%. The insufficient addition of boron is not conducive to the adsorption and activation of nitrate ions, hindering the deoxygenation process of nitrogen-containing intermediates, thus leading to a decrease in performance.

[0055] Embodiment 4:

[0056] The other steps were the same as step (1) and step (2) of Example 1, except that the amount of boron powder added was replaced by 0.040 g from 0.025 g. The ammonia yield of the obtained material was 5561 μg h at -0.7 V. -1 mg cat -1 , the Faradaic efficiency is 81.71%. The ammonia yield at -0.5 V is 3924 μg h -1 mg cat -1 , the Faraday efficiency is 86.31%. Excessive addition of boron makes the catalyst easy to agglomerate during the annealing process, which is not conducive to the exposure of active sites, weakens the activity of the catalyst, and thus leads to a decrease in performance.

[0057] Embodiment 5:

[0058] The other steps were the same as step (1) and step (2) of Example 1, except that the annealing temperature after adding boron powder was changed from 950°C to 900°C, and the annealing time was changed from 1.5 hours to 2 hours. The ammonia yield of the obtained material at -0.7V was 7185 μg h -1 mg cat -1 , the Faradaic efficiency is 90.67%. The ammonia yield at -0.5 V is 4375 μg h -1 mg cat -1 , the Faraday efficiency is 92.08%. The annealing temperature is reduced while the annealing time is extended, so that the boron powder and cobalt@MXene are well combined, and the ammonia yield and Faraday efficiency of the obtained material are close to those in Example 1.

[0059] Embodiment 6:

[0060] The other steps were the same as step (1) and step (2) of Example 1, except that the annealing temperature after adding boron powder was changed from 950°C to 970°C, and the annealing time was changed from 1.5 hours to 1 hour. The ammonia yield of the obtained material at -0.7V was 7098 μg h -1 mg cat -1 , the Faradaic efficiency is 90.29%. The ammonia yield at -0.5 V is 4272 μg h -1 mg cat -1 , and the Faraday efficiency is 91.81%. The ammonia yield and Faraday efficiency of the obtained material are close to those of Example 1.

[0061] In summary, the electrocatalyst prepared by the present invention solves the current problems of NO 3The common problem of cobalt-based catalysts for RR. As a novel electrocatalyst, dicobalt boride@MXene heterostructure has fast electron transfer kinetics, abundant catalytic active sites and excellent structural stability. Thanks to the excellent active hydrogen generation ability of cobalt sites, the excellent nitrate adsorption and reduction activity of boron sites, and the high conductivity and structural support of MXene, dicobalt boride@MXene heterostructure shows satisfactory ammonia yield, Faraday efficiency and cycle stability in the electrocatalytic nitrate reduction reaction, which provides the possibility for the green and sustainable development of ammonia synthesis.

[0062] The above contents are only examples and explanations of the concept of the present invention. It should be pointed out that ordinary technicians in this technical field can make several improvements and supplements without departing from the method of the present invention, and these improvements and supplements should also be regarded as the protection scope of the present invention. Any technician familiar with this profession, without departing from the spirit and scope of the present invention, can make some changes, modifications and evolutions of the technical content disclosed above, which are equivalent embodiments of the present invention; at the same time, any changes, modifications and evolutions of any equivalent changes made to the above embodiments based on the essential technology of the present invention are still within the scope of the technical solution of the present invention.

[0063] Matters not covered by the present invention are known technologies.

Claims

1. A method for preparing an in-situ constructed MXene-based metal boride electrocatalyst, characterized in that: The method comprises the following steps: Step 1: Ti3AlC2 MAX, CoCl2·6H2O, NaCl and KCl are mixed and ground for 15 to 30 minutes to obtain a first mixture; Among them, the molar ratio of Ti3AlC2 MAX, CoCl2·6H2O, NaCl and KCl is 1:3:2:2; Step 2: annealing the first mixture obtained in step 1 at 700-800° C. for 20-30 hours in an argon atmosphere, then washing with deionized water and freeze-drying to obtain cobalt@MXene; Step 3: The cobalt@MXene, boron powder, NaCl and KCl prepared in step 2 are mixed and ground to obtain a second mixture; The sum of the masses of NaCl and KCl is 8 to 12 times the sum of the masses of cobalt@MXene and boron powder; the molar ratio of NaCl to KCl is 1:0.8 to 1.2; the mass ratio between cobalt@MXene and boron powder is 8:0.9 to 1.1; Step 4: anneal the second mixture obtained in step 3 in an argon atmosphere at a temperature of 900 to 1000° C. for 1 to 2 hours; then wash with deionized water and freeze-dry to obtain dicobalt boride@MXene.

2. The use of the dicobalt boride@MXene electrocatalyst prepared by the method of claim 1, characterized in that: Used for electrocatalytic reduction of nitrate to synthesize ammonia.

3. The use according to claim 2, characterized in that: The method comprises the following steps: electrolyzing an electrolyte for 0.5 to 2 hours under a three-electrode system and constant voltage to obtain ammonia; wherein carbon paper loaded with a catalyst, Ag / AgCl, and a platinum wire are used as a working electrode, a reference electrode, and a counter electrode respectively; and the diaphragm is a Nafion 117 membrane; The electrolyte solution is composed of 0.1-1.0M potassium sulfate solution containing 0.01-0.10M potassium nitrate; 0.5-1mg catalyst is loaded per 1 square centimeter; the voltage range of electrolysis is -0.3V to -0.7V.

Citation Information

Patent Citations

  • A method for electrochemical reduction of nitrates and recovery of ammonia using a self-supporting nanowire electrode

    CN114369841B